Rekayasa Proses Pembuatan Serbuk Minuman Tradisional dari Rempah dan Non-Dairy Creamer melalui Foam Mat Drying - Wiyono, Andi E; Kuswardhani, Nita; Mahardika, Nidya S; Ruriani, Eka; Sulistyani, Ika; Choiron, Miftahul; Purbasari, Dian (Universitas Pattimura, 2024)
Spice drinks are traditional beverages made from ginger and lemongrass, with the addition of vegetable creamer to enhance their quality. This study aimed to determine the effect of varying the ratio of spices to vegetable creamer on the organoleptic and physicochemical characteristics of the drink. Additionally, it sought to evaluate the yield, antioxidant activity, specific heat, and mass balance of the spice drink powder from the selected formulation. The experimental design was a Completely Randomized Design with two factors: the percentage ratio of spices to vegetable creamer. The results showed that varying the spices to vegetable creamer ratio significantly affected the organoleptic characteristics, particularly hedonic and hedonic quality attributes. Regarding physicochemical properties, the ratio of spices significantly affected color, dissolution time, total soluble solids, pH, and moisture content. The ratio of vegetable creamer significantly influenced color lightness, dissolution time, pH, and moisture content. The best treatment was the A3B1, which resulted in a yield of 18.09%, exhibited an antioxidant activity of 73.5%, had a specific heat of 1.5361kJ/kgoC, and showed an efficiency value of not more than 1 (100%). The most significant mass loss occurred during washing, amounting to 216,21 g or 65,63% of the incoming raw material.